My sport, my perspectives: Intersubjectivity in cyclist Instagram posts. (April 2020) - Ross, Andrew S.; Zappavigna, Michele
Highlights: Context of sport on Instagram reveals a range of different perspectives. Documented selfie types are utilised in the context of cycling. Cyclist Instagram posts reveal broader possibilities in intersubjective relations as well as a new selfie type. Abstract: The affordances of social media platforms have generated an intensified focus on the daily lives and activities of individuals. Instagram is an extremely popular platform, particularly in relation to the 'selfie', which has led to a growing body of research in relation to selfie types and the different subjective and intersubjective relations they present. This article takes the sport of cycling and investigates how different intersubjective relations and perspectives on the sport and the self are presented by amateur cyclists. The images highlight the different intersubjectivities that can be construed from the images themselves, as well as how they demonstrate an affiliation with the sport. It is argued that cycling demonstrates the relevance of previously documented selfie types as well as offers new possibilities for expanding our understanding of the intersubjective relations offered by selfies in the sporting context. These add not only to our understanding of selfies, but also add further layers of perspective on the sport to those offered by the selfie.